The ALAT PREDIKSI CURAH HUJAN DENGAN MENGGUNAKAN WEATHER SENSOR SEBAGAI PENANGGULANGAN TERHADAP POTENSI BENCANA BANJIR - Zuhri, Muhammad Zuhri (Universitas Islam Balitar Blitar, 2023)
Natural disaster is a disaster that cannot be known when it will happen, especially flood disasters that often occur when entering the rainy season. When the intensity of rainfall is high, areas that are subscribed to flooding can quickly be submerged by water. Therefore, a tool is needed that can estimate flood time connected to the Internet of Things, with this tool it is hoped that it can help residents who are in flood-prone areas to better prepare themselves when rainfall has exceeded the maximum limit.